Archaeometry of fire aided limnosilicite mining in the Avas-Tűzköves (Miskolc, NE-Hungary) Paleolithic silica source. Issue 13 (2nd October 2020) - Kristály, Ferenc; Tóth, Zoltán H.; Ringer, Árpád; Török, Béla
ABSTRACT: This paper communicates new results on fire aided limnosilicte mining in a Hungarian paleolithic site. The beneficial effect of temperature on material fragmentation and chipping was proved by laboratory experiments, with samples fired at 260°C and 360°C. Mineralogical transformations which lead to fragmentation are triggered by heating and were characterized by analytical methods in detail. The raw material is nanocrystalline quartz dominant silicolite with amorphous silica, moganite and traces of goethite and tridymite, identical to length-fast chalcedony. X-ray diffraction revealed the recrystallization of amorphous silica into quartz, accompanied by H2 O loss measured by thermogravimetry. Using attenuated total reflectance Fourier-transformed infrared spectroscopy, both H2 O and OH content, their loss by heating and recrystallization was evidenced. Scanning electron microscopy on chipped surfaces revealed the disappearance of the fibrous texture, promoting the knappability of the material. The main factors influencing fire-aided mining and/or processing were identified as H2 O pressure, amorphous silica crystallization as a result of H2 O and OH removal from the silanol groups and change in quartz crystallite morphology.